Simulation of Respiratory Distress for 3rd Year Pediatrics Medical Students - Suzanne Friedman; Meghan Tozzi; Ashley Siems; Sheemon Zackai (Association of American Medical Colleges, 2014)
Abstract This is a curriculum session for use with third-year medical students on their pediatrics clerkship designed to teach the evaluation, assessment, and management of pediatric patients with respiratory distress. The curriculum uses simulation techniques and cases to enhance learning in the real-world setting. This simulation session is designed to teach third-year students about one of the most common pediatric concerns, respiratory distress, while also learning about leadership and communication skills. Since initiation, students have reported increased comfort levels with these patients in real-life situations. Survey results from the medical students have consistently been favorable.